2016
DOI: 10.1002/cssc.201600751
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Hydrogen Source on the Selective Production of γ‐Valerolactone and 2‐Methyltetrahydrofuran from Levulinic Acid

Abstract: A mechanistic study of the hydrogenation reaction of levulinic acid (LA) to 2-methyltetrahydrofuyran (MTHF) was performed using three different solvents under reactive H2 and inert N2 atmospheres. Under the applied reaction conditions, catalytic transfer hydrogenation and hydrogenation with molecular H2 were effective at producing high yields of γ-valerolactone. However, the conversion of this stable intermediate to MTHF required the combination of both hydrogen sources (the solvent and the H2 atmosphere) to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 43 publications
3
55
0
Order By: Relevance
“…Regarding the related reaction mechanism, under solvent-free conditions, 2-BuOH is predominantly formed via subsequent hydrogenation/decarbonylation reactions of the GVL [42], as shown in Scheme 3. Obregón et al [45] reported the GVL hydrogenation, achieving a maximum 2-BuOH yield of 37.3 mol %, working in 2-PrOH, at 250 °C and 4 MPa H2. Lastly, Lv et al [54] have recently used nanoporous Ru for LA hydrogenation in water, reporting the combined production of both 2-BuOH and 2-Pentanol (2-PeOH), the latter derived mainly from 1,4-PDO hydrogenation, with a total [2-BuOH + 2-PeOH] yield of 78.8 mol %, working at 140 °C for 20 h, with 6 MPa H2.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the related reaction mechanism, under solvent-free conditions, 2-BuOH is predominantly formed via subsequent hydrogenation/decarbonylation reactions of the GVL [42], as shown in Scheme 3. Obregón et al [45] reported the GVL hydrogenation, achieving a maximum 2-BuOH yield of 37.3 mol %, working in 2-PrOH, at 250 °C and 4 MPa H2. Lastly, Lv et al [54] have recently used nanoporous Ru for LA hydrogenation in water, reporting the combined production of both 2-BuOH and 2-Pentanol (2-PeOH), the latter derived mainly from 1,4-PDO hydrogenation, with a total [2-BuOH + 2-PeOH] yield of 78.8 mol %, working at 140 °C for 20 h, with 6 MPa H2.…”
Section: Methodsmentioning
confidence: 99%
“…Concerning the other possible route, the presence of 2-MeTHF was reported for the first time as a by-product of the LA hydrogenation with CuCr 2 O 3 [35]. Afterward, many works have been published on this topic, which have partially clarified the reaction mechanism, and significantly improved the catalytic performances for the synthesis of 2-MeTHF [36][37][38][39][40][41][42][43][44][45]. Two reaction mechanisms have been proposed for 2-MeTHF synthesis from LA, the first one occurring by LA dehydration via angelicalactone (AGL) (path A, Scheme 1), whereas the second one by LA hydrogenation to 4-hydroxypentanoic acid (HPA) (path B, Scheme 1), both reported in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that there was a synergistic effect between Ni and Cu in the mixed NiCu particles leading to an improved yield of 2-MTHF. A recent study by Palkovits and co-workers [27] discussed the mechanism of the hydrogenation of LA to GVL and 2-MTHF using Cu-Ni/Al 2 O 3 catalyst under hydrogenation and transfer hydrogenation conditions. They have reported that Cu-Ni/Al 2 O 3 catalysts are more active than Ru/C using a solvent that is a poor hydrogen donor, and that a 93% yield of GVL can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies confirmed a significant effect of the solvent system. Under the applied reaction conditions, catalytic transfer hydrogenation and hydrogenation with molecular H 2 occurred and their combination was necessary to achieve 80 % 2‐methyltetrahydrofuran yield with 2‐propanol as solvent and 40 bar of H 2 (at room temperature) . Also, the transformation of platform chemicals such as sorbitol and xylitol via selective C – C and C – O cleavage into ethylene and propylene glycol could be established (Fig.…”
Section: Biomass As Renewable Resourcementioning
confidence: 99%